2014
DOI: 10.1098/rstb.2013.0159
|View full text |Cite
|
Sign up to set email alerts
|

Zif268 / Egr1 gain of function facilitates hippocampal synaptic plasticity and long-term spatial recognition memory

Abstract: It is well established that Zif268/Egr1 , a member of the Egr family of transcription factors, is critical for the consolidation of several forms of memory; however, it is as yet uncertain whether increasing expression of Zif268 in neurons can facilitate memory formation. Here, we used an inducible transgenic mouse model to specifically induce Zif268 overexpression in forebrain neurons and examined the effect on rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 46 publications
2
50
2
Order By: Relevance
“…Consistent with its function as an immediate-early gene, biophysical characteristics of Egr1 include fast (millisecond) activation in response to stimuli and transient expression (Veyrac et al, 2014). Egr1 is implicated in synaptic transmission (Jones et al, 2001; Penke et al, 2013), learning (Guzowski et al, 2001), memory consolidation (Jones et al, 2001; Penke et al, 2013; although see Lee et al, 2004) and reconsolidation (Lee et al, 2004), and more recently in the recruitment of new neurons into functional networks after hippocampal neurogenesis (Veyrac et al, 2013). Coincident with these roles, levels of Egr1 protein are higher in brain regions involved in these functions, including the hippocampus, particularly the CA1 region, and cortex relative to other regions (Beckmann and Wilce, 1997).…”
Section: Early Growth Response (Egr) Factorsmentioning
confidence: 99%
“…Consistent with its function as an immediate-early gene, biophysical characteristics of Egr1 include fast (millisecond) activation in response to stimuli and transient expression (Veyrac et al, 2014). Egr1 is implicated in synaptic transmission (Jones et al, 2001; Penke et al, 2013), learning (Guzowski et al, 2001), memory consolidation (Jones et al, 2001; Penke et al, 2013; although see Lee et al, 2004) and reconsolidation (Lee et al, 2004), and more recently in the recruitment of new neurons into functional networks after hippocampal neurogenesis (Veyrac et al, 2013). Coincident with these roles, levels of Egr1 protein are higher in brain regions involved in these functions, including the hippocampus, particularly the CA1 region, and cortex relative to other regions (Beckmann and Wilce, 1997).…”
Section: Early Growth Response (Egr) Factorsmentioning
confidence: 99%
“…44 The enhancement in the levels of Arc and Egr1 mRNAs by CTX 3C was indicative of an increase in synaptic activity. These IEGs are implicated in the molecular mechanisms of homeostatic plasticity, 20,38 and it has been reported that Arc mediates the homeostatic response to increased activity by a pathway that ultimately downscales excitatory synaptic strength. 45 For the purpose of evaluating the effect of CTX 3C on mEPSCs, these events (isolated as described in the Materials and Methods section) were analyzed in control neurons and in neurons treated with 5 nM CTX 3C ( Figure 5).…”
Section: Ctx 3c Enhances the Expression Of Arc And Egr1mentioning
confidence: 99%
“…Our results show for the first time, that GNX-induced impairments in the spontaneous object recognition test can be prevented by viral-mediated Zif268 expression. Mice with genetically-induced forebrain overexpression of Zif268 exhibit enhanced long-term object-location recognition as compared to controls (Penke et al, 2014). In the present study, we observed no enhancement of novel object preference in males that were gonadally intact and received mPFC AAV-Zif268 construct.…”
Section: Discussionmentioning
confidence: 99%
“…Loss-of-function studies have demonstrated the necessity of Zif268 gene expression for normal long-term memory formation (Jones et al, 2001, Bozon et al, 2002). In parallel, gain-of-function studies have shown that overexpression of Zif268 within the dentate gyrus can enhance long-term spatial memory (Penke et al, 2014). Within the neural circuitry that supports learning and memory, Zif268 expression is induced following learning-related stimuli.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation